2020
DOI: 10.3390/ijerph17103628
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Decision Training, from a Cognitive Perspective, on Decision-Making in Volleyball: A Systematic Review and Meta-Analysis

Abstract: Over the past few decades there has been great interest in the study of cognitive processes, and specifically decision-making, from a cognitive perspective. The aim of the present study was to systematically review the scientific literature on the effect of decision training interventions/programs, from a cognitive perspective, on the decision-making of volleyball players. The systematic search was carried out in five scientific electronic databases according to PRISMA guidelines Web of Science (WOS), Pubmed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…Even if these types of skills cannot be used to predict future performance, we suggest that training programs targeting decision-making skills might be beneficial to improve performance. A systematic review focusing on decision-making training in volleyball showed that this type of training (e.g., perceptual training, video feedback) improved decision-making skills in volleyball players (Conejero Suárez et al, 2020). Similar positive effects have been shown for decision-making training programs in other team sports.…”
Section: Discussionmentioning
confidence: 99%
“…Even if these types of skills cannot be used to predict future performance, we suggest that training programs targeting decision-making skills might be beneficial to improve performance. A systematic review focusing on decision-making training in volleyball showed that this type of training (e.g., perceptual training, video feedback) improved decision-making skills in volleyball players (Conejero Suárez et al, 2020). Similar positive effects have been shown for decision-making training programs in other team sports.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of general cognitive functions in volleyball has been widely demonstrated in previous studies [ 9 , 10 , 21 , 31 ]. The combination of cognitive functions (executive control and perceptual speed) and volleyball-specific skills was found to be useful for discriminating players of different competitive levels [ 10 ].…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, such a paradigm might be implemented in both training and player selection in future studies. For example, players might be trained, through sport-specific perceptual–vision training [ 71 , 72 , 73 ], to read these motor kinematics primitives to improve their decision-making processes and optimise their ability to perceive and process relevant body features [ 74 , 75 ]. Moreover, the paradigm might be expanded to test an athlete’s ability to distinguish between fake and real attack actions according to the level of expertise.…”
Section: Discussionmentioning
confidence: 99%